Lyophilized Gelatin@non-Woven Scaffold to Promote Spheroids Formation and Enrich Cancer Stem Cell Incidence - Jingjing Fu; Feng Chen; Huihui Chai; Lixia Gao; Xiaohui Lv; Ling Yu (Nanomaterials, 2022)
A gelatin@non-woven fabric (gelatin@NWF) hybrid scaffold with tailored micropore structures was fabricated by lyophilizing, using gelatin to support cells and the NWF matrix as a frame to enforce the mechanical stability of gelatin. By freezing the gelatin and NWF hybrid in liquid nitrogen and subsequently lyophilizing and crosslinking the process, the gelatin@NWF scaffold was prepared to support cell growth and promote cell aggregation and spheroids’ formation. The results indicated that by tuning the lyophilizing temperature, the micropore size on the gelatin could be tailored. Consequently, tumor spheroids can be formed on gelatin@NWF scaffolds with honeycomb-like pores around 10 µm. The cell spheroids formed on the tailored gelatin@NWF scaffold were characterized in cancer stem cell (CSC)-associated gene expression, chemotherapy drug sensitivity, and motility. It was found that the expression of the CSC-associated biomarkers SOX2, OCT4, and ALDH1A1 in gene and protein levels in DU 145 cell spheres formed on gelatin@NWF scaffolds were significantly higher than in those cells grown as monolayers. Moreover, cells isolated from spheroids grown on gelatin@NWF scaffold showed higher drug resistance and motility. Tumor spheroids can be formed on a long-term storage scaffold, highlighting the potential of gelatin@NWF as a ready-to-use scaffold for tumor cell sphere generation and culturing.